STRENGTHENING CULTURE-BASED NATIONALISM CHARACTER FOR INDONESIAN MIGRANT CHILDREN THROUGH THE KEPONG LEARNING CENTER, MALAYSIA - Heru Sanjaya; Lahmuddin Lahmuddin; Ryan Taufika; Zulkifli Amin; Juliaman Siahaan; Miftha Huljannah (Journal Analytica Islamica, 2026)
The formation of Indonesian migrant children's cultural-based nationalism in Malaysia is very important. This study aims to analyze the role of Sanggar Bimbingan Muhammadiyah Kepong in helping Indonesian migrant children in the formation of Indonesian cultural-based nationalism. The study uses a descriptive qualitative approach with a case study method, involving four main respondents, namely fifth-grade students, teachers, parents, and the principal. Data collection techniques included observation, interviews, and documentation with validity through source and technique triangulation. The results of the study show that the implementation of culture-based learning through the “Culture Friday” program, which includes interactive digital quizzes about national heroes, learning traditional regional dances, introduction to angklung musical instruments, and religious activities, has proven effective in strengthening the national identity of migrant children. Internal and external factors play a significant role in efforts to preserve Indonesian culture. The Kepong Learning Center serves as a forum for strengthening comprehensive nationalism that integrates Indonesian cultural values, digital learning technology, and the development of a nationalistic character, so that Indonesian children in Malaysia can maintain a strong sense of nationalism in a multicultural environment.